2009
DOI: 10.4319/lo.2009.54.3.1002
|View full text |Cite
|
Sign up to set email alerts
|

Barium and molybdenum records in bivalve shells: Geochemical proxies for phytoplankton dynamics in coastal environments?

Abstract: Barium : calcium and molybdenum : calcium ratios were investigated in shells of the tropical scallop Comptopallium radula. Three juvenile specimens were harvested alive in the southwest lagoon of New Caledonia after a 1-yr hydrological survey. Calcite samples representing a few hours of biomineralization were laser-ablated along the maximal growth axis and analyzed for Ba and Mo content with an inductively coupled plasma mass spectrometer. Absolute dates of shell precipitation assigned on the basis of periodic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
62
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 109 publications
(73 citation statements)
references
References 58 publications
6
62
2
1
Order By: Relevance
“…Barats et (Thébault et al, 2009). Our data may support these assumptions, but none of these pathways can be completely demonstrated.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…Barats et (Thébault et al, 2009). Our data may support these assumptions, but none of these pathways can be completely demonstrated.…”
supporting
confidence: 79%
“…This statement also agrees with the Mo concentration in phytoplankton cell data obtained from experimental culture on various genera and species which did not show Mo cell enrichment under controlled growing conditions Quigg et al, 2003). Mo cell enrichment would however, be induced by environmental and physiological conditions such as light limitation (Finkel et al, 2006) or nitrate utilization (Thébault et al, 2009). This last hypothetic process could be conclusive for the Bay of Brest exhibiting significant nitrate inputs from human activities (Ragueneau et al, 2002).…”
Section: Influence Of a Biogenic Pelagic Process On Mo Inputs To Bottmentioning
confidence: 99%
See 1 more Smart Citation
“…Lorrain et al [2004] showed that in scallop shells, these ontogenetic d 13 C trends were due to increasing contribution of respired carbon with the body size. An influence of food availability was also suggested by Van der Putten et al [2000] because of decreasing d 13 C values associated with Mn and Ba peaks which are believed to be related to phytoplankton blooms [Stecher et al 1996;Gillikin et al, 2006b;Thébault et al, 2009]. However, the majority of the shell d …”
mentioning
confidence: 93%
“…It has previously been demonstrated that differences in the incorporation of elements to bivalve shell vary between larval and recruited shell (Zacherl et al 2009). It has also been found that the diet of individuals may influence the uptake of elements into bivalve shell (Thebault et al 2009 Table 2 possible that prodissoconch shell initially consists primarily of amorphous calcium carbonate (ACC), which later transitions to aragonite (Weiss et al 2002). Both differences in the structure of ACC as well as changes as this precursor transitions to aragonite have the potential to prevent comparisons being made between prodissoconch and settled shell material (Weiss et al 2002).…”
Section: Intra-shell Variationmentioning
confidence: 99%